Jugular Foramen Syndrome as Initial Presentation of Metastatic Lung Cancer - Hayward, Dustin; Morgan, Christopher; Emami, Bahman; Biller, Jose; Prabhu, Vikram C. (Journal of Neurological Surgery Reports, 2012)
Metastatic involvement of the cranial base and jugular foramen generally presents with headache and lower cranial neuropathy but may escape early diagnosis. In this report, a patient developed a jugular foramen syndrome as the initial presentation of metastatic lung cancer soon after being diagnosed and treated surgically for extracranial atherosclerotic internal carotid artery disease. With the appropriate diagnosis established, he underwent local fractionated radiation therapy and systemic chemotherapy but succumbed to the disease. This report analyses metastatic disease affecting the cranial base and in particular, the jugular foramen, with a discussion of the clinical syndromes that accompany this rare condition.
Keywords: skull base metastasis; cranial nerve palsy; Collet–Sicard syndrome; soil and seed hypothesis